Green and Chemical Silver Nanoparticles and Pomegranate Formulations to Heal Infected Wounds in Diabetic Rats - Renan Aparecido Fernandes Scappaticci (MDPI AG, 2021)
Infected cutaneous ulcers from diabetic rats with Candida albicans and Streptococcus aureus were treated with spray formulations containing green silver nanoparticles (GS), chemical silver nanoparticles (CS), or pomegranate peel extract (PS). After wound development and infection, the treatments were performed twice per day for 14 days. The wound healing was analyzed on days 2, 7, and 14 through the determination of CFUs, inflammatory infiltrate, angiogenesis, fibroplasia, myeloperoxidase, and collagen determination. Expressive improvement in wound healing was noted using both silver nanoparticles for 7 days. All the treatments were superior to controls and promoted significant S. aureus reduction after 14 days. CS presented better anti-inflammatory results, and GS and CS the highest number of fibroblasts. Despite the techniques’ limitations, GS and CS demonstrated considerable potential for managing infected wounds, especially considering no early strategies prior to the drugs, such as the debridement of these wounds, were included.